Riethia (Kieffer 1917) (Diptera: Chironomidae) revised for the Austro-Pacific region - Cranston, Peter S. (Zootaxa, 2019)
Riethia Kieffer, known previously from New Zealand for a species stated to be also in Australia plus several Australian and South American species, is revised for the Austro-Pacific region. The three previously-described Australian species Riethia stictoptera Kieffer (the genotype), Riethia cinctipes Freeman and Riethia plumosa Freeman are distinct and valid, and are redescribed in all stages. In contrast, Riethia zeylandica Freeman now is restricted to New Zealand: Australian specimens previously allocated to R. zeylandica belong to several new species recognised on morphology of adult male, pupa and larva, with guidance from molecular data. Most belong to a widespread eastern Australian Riethia azeylandica sp. n.: others are allocated to Riethia hamodivisa sp. n., Riethia paluma sp. n., Riethia phengari sp. n. and Riethia queenslandensis sp. n., each with a more restricted range. From Western Australia three species, Riethia donedwardi sp. n., Riethia noongar sp. n. and Riethia wazeylandica sp. n., are described as new from adult male, pupa and larva. Riethia kakadu sp. n. is described from the monsoonal tropics of Northern Territory from the adult male and tentatively associated pupa. From New Caledonia a reared species is described as Riethia neocaledonica sp. n.. Illustrated identification keys are provided for the males, pupae and larvae. Unassociated larvae that key to reared described species are excluded from type status, and based on morphology and molecular evidence three unreared larval types, ‘A’, ‘B’ and ‘C’, are also described and keyed. Previously reported molecular vouchers are reviewed, and certain Genbank accessions re-identified. Extensive data shows Riethia are distributed almost throughout Australia from standing and flowing waters, from tropics and subtropics to cool temperate Tasmania, but probably only in permanent and standing waters. The immature stages of several taxa can co-occur: as many as four can be found simultaneously in one site. Terminology of the volsellae of the male genitalia and the dorsal head and maxilla of the larva is reviewed.